The Role of Sharia Committee and Board of Director in Improving The Performance of Islamic Insurance Companies - Dedi Kusmayadi, Irman Firmansyah, Iwan Hermansyah (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The purpose of this study is to determine the role of sharia committeeandboardofdirectors in Islamic insurance companies on financial performance.The emergence of this study is because the Islamic finance industry not only runs a business but also needs to comply with Islamic sharia principles.This study involved Islamic Insurance companies that run sharia business units from 2011 to 2019. The research method used in this study is the moderated regression analysisusingcomputer software SPSS ver 22. The variable used to measure financial performance is the surplus on contribution (SoC), while the independent variable is the debt to equity ratio, size, and age. The results show that the surplus on contribution is only influenced by size. Besides, only the Sharia committee successfully strengthens the relationship between size and financial performance. Meanwhile, the board of directors has no significant impact on financial performance.Therefore, this study explains that the Sharia committee not only maintained sharia compliance but also succeeded in improving the performance of Islamic insurance companies, especially for large companies